Preparation of Selenium Nanoparticles with Mechano-sonochemical Methods - Khubulava, Salome (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Nanotechnology and nanomedicine revolutionized the pharmaceutical market, medicine, and biology. The simple size comparison gives an idea of using nanoparticle as very small probes that would allow us to observe the cellular machinery without introducing too much interference. â€œNanosizingâ€ drugs decrease toxicity and reduces the needed dose. Nanoparticles are used for site-specific drug delivery, imaging, treating illnesses, and diseases such as cancer, neurodegenerative disorders, ocular diseases, respiratory diseases, and diabetes mellitus. Recent studies indicate the positive impact of selenium nanoparticles on different organ systems. They have antioxidant, antimicrobial, anti-carcinogenic properties, and selenium nanoparticles characterized by good permeability in tissues and low toxicity. Nowadays, there are different ways of preparing nanoparticles, but most of them are related to difficult, toxic, and expensive procedures. Materials and Methods: Pure selenium metal powder was used and synthesized nanoparticles were characterized by JEOL JSM-6510 LV scanning electron microscope (SEM), Zeiss Ultra 55 SEM, and JOEL JEM-100SX transmission electron microscope; also by dynamic light scattering (Thermo Scientific Nicolet iS50 - Fourier-transform infrared spectroscopy [FTIR]) and Malvern Instruments Zeta Sizer Nano ZS. To reduce the size of the selenium powder, we used planetary ball mill DECO-PBM-V-0.4L and Ultrasonic Homogenizer UZDN-1 U4.2. Results and Discussion: Pure selenium grinded powder was characterized in JEOL JSM-6510 LV SEM and wet grinded in Deco planetary ball mill further size reduction to 2â€“10 Î¼m was confirmed by SEM. Selenium powder suspension was irradiated using ultrasonic homogenizer and characterized for intensity and size of nanoparticles with dynamic light scattering FTIR. Average Zeta potential of -35.05 mV has been recorded. Toxic dose of 5000 mg/kg of selenium nanoparticles has been established as per accordance to OECD guidelines. Conclusion: Safe, simple, and cost-effective SeNPs have been developed for the effective treatment of disease such as diabetes with opening of new prospective further in nanotechnology and nanosized drug delivery system.